Effect of the potassium permanganate coated zeolite nanoparticles on the quality characteristic and shelf life of peach and nectarine - Emadpour, M.; Ghareyazie, B.; Kalaj, Y. R.; Entesari, M.; Bouzari, N. (International Journal of Agricultural Technology, 2015)
This research was conducted to study the effect of removal of the ethylene using potassium permanganate coated nano zeolites from the storage on the quality characteristics and shelf life of peach and nectarine. Potassium permanganate and Zeolite based Nano-Molecular Filters were used in ETH 1500 machine. Two cultivars of peach and three cultivars of nectarine were used in this experiment Commercial traits affecting the marketing and shelf- life of peach and nectarine i.e. pH, texture (firmness), appearance, total soluble solid concentration (TSS), titratable acidity, internal breakdown and the reduction in fresh weight were measured at the beginning of the experiment (day 0), 12, 24 and 36 days after storage. The experiment was laid in a two factor Randomized Complete Block Design (RCBD) with four replications. Two factors were the effect of ethylene absorbent ETH 1500 machine and the type of fruit (peach and nectarine). Maximum firmness in nectarine (24.09) and peach (19.80), the minimum pH in nectarine (5.42) and peach (6.14), minimum weight loss in nectarine (4.12%) and peach (5.94%) and the best appearance evaluation score in nectarine (score 3.47) and in peach (score 3.5) were observed in presence of the ethylene absorbing machine in comparison with the control treatment (no ethylene absorption). These results indicate that application of nano zeolite particles coated with potassium permanganate in a machine circulating the ethylene containing air, prevents weight loss, reduction in firmness, spoilage and increase shelf- life and the quality of stored peach and nectarine.